Analytical investigation of a new direct Column-to-Cased shaft connection. (15th October 2021) - Zhao, Mu-Zi; Lehman, Dawn E.; Roeder, Charles W.
Highlights: Modeling approach for the interface behavior between steel rib and concrete fill. Different approaches to enhance the load transfer of the new connection. Recommendations on the design of a new direct RC pier-to-cased shaft connection. Abstract: In regions of high seismicity, the large seismic design forces sustained by the superstructure must be transferred to the bridge foundations. In these situations, in particular in situations with weak soils, cased shafts, which are concrete filled steel tube (CSFT) components, are used for piles and drilled shafts. Prior research shows that these components have large flexural, axial and shear strengths. Typically, the forces are transferred from the column to the pile through a pile cap. However, direct connections are becoming more common, in particular because they have efficiency in terms of placement and can facilitate accelerated bridge construction. This research studies two different connections: (1) direct embedment of the column reinforcement into the pile and (2) an enhanced connection using a ring at the top of the tube in the pile to enhance mechancial bond and reduce embedment depth. The study was conducted using a high-resolution finite element analysis modeling approach validated using large-scale test results of reinforced concrete (RC) and CFST components and connections. The model included advanced constitutive modeling of the concrete as well as modeling of the bond between the steel tube and concrete fill and the reinforcing steel and the concrete fill. The transfer of forces from the yielding reinforcing bars in the RC pier to the concrete fill and tube of the pile is critical for this connection. Different approaches were investigated to achieve transfer without loss of strength or ductility. A supplemental rib inside the tube ultimately was used to enhance the load transfer with the minimum embedment length. The model was used to conduct a parametric study with the following study parameters: the rib location ( l R ), tube diameter ( D ), reinforcing bar diameter, and embedment depth ( l d ). The results were used to propose initial design recommendations.